Evaluation of football development program: A case study on specific sport class for high school level in Sleman Regency, Yogyakarta - Santoso, Nurhadi; Wiyanto, Agus; Masri (The journal of contemporary issues in business and government, 2020)
This study evaluates the football achievement development in a special sports class high school level in Gunungkidul Yogyakarta. This study uses the CIPP (Context, Input, Process, Product) evaluation model approach. The data were collected using interview guidelines, observation sheets, and document study. This study's Respondents involved the principal, the teacher in charge of implementing a special sports class, and the football coaches. The data analysis technique used qualitative data analysis through data triangulation. The study results reveal that in the context aspect, the implementation of a special sports class is based on a decision letter from the Head of the District Education Office and a decision letter from the DIY Provincial Education Office. In the input aspect, the admission of new students for the special sports class is carried out through administrative selection, tests of physical abilities, and sports skills. Besides, the budget for implementing Special Sports Class still relies on sources of funds from the provincial level Regional Revenue and Expenditure Budget, School Operational Assistance, and school committee. The condition of equipment availability is considered good, and the football field facilities used for the training process are in category C. Also, the coach's license who handles the sport of football is in categories B and C. In the process aspect, the time allocation for soccer sports achievement falls into categories B, and C. Football match trials have been carried out both by the school and the coach himself. Meanwhile, in the product aspect, students' achievements have been achieved by students in the special sports class at the regency level, and achievements at the provincial level are still considered minimal.